READING FOR UNDERGRADUATES EFL STUDENTS - Reny R. Nadeak (WAHANA, 2011)
Students acknowledge in a way, that they donÃ‚â€™t understand the reading text due to lack of vocabularies. But on the other hand teachers of reading take it for granted that the students have sufficient knowledge of vocabularies and sentence structures. In the end teaching reading turn out to discuss difficult or unfamiliar words and sentence structures. Helping undergraduates understanding a text is the purpose of this article. Teachers are to make plans in advance that cover guiding students to recognize words and sentence structures learning about the importance of context and using context clues to find meaning. This context in sentences or paragraphs, the students will encounter in their reading texts. These practices of knowing words and sentence structures are expected to develop their interest and readiness in reading. Teachers play important roles and students have to participate actively to make the practices work The skills of recognizing words and sentence structures in English are meant to be the students background og knowledge to be able to understand reading assignments. Some practices are recommended before the students are ready to read the texts.